Symmetric play in repeated allocation games - Christoph Kuzmics; Thomas Palfrey; Brian W. Rogers (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2012)
We study symmetric play in a class of repeated games when players are patient. We show that, while the use of symmetric strategy profiles essentially does not restrict the set of feasible payoffs, the set of equilibrium payoffs is an interesting proper subset of the feasible and individually rational set. We also provide a theory of how rational individuals play these games, identifying particular strategies as focal through the considerations of Pareto optimality and simplicity. We report experiments that support many aspects of this theory.
Keywords: 330; symmetry; repeated games; focal points; experiments; symmetry; repeated games; focal points; experiments